Effects of practice schedule on the adaptive process of motor learning - Corrêa,Umberto Cesar (2010)
This study had as objective to investigate the effects of practice schedule on the adaptive process of motor learning. The experimental design consisted of four practice groups (constant, random, constant-random and random-constant), and two learning phases (stabilization and adaptation). In three experiments, children performed a complex task of coincident timing, in which the varied practice was manipulated in terms of visual stimulus (Experiment 1), movement pattern (Experiment 2), and a combination of both (Experiment 3). In Experiment 1, the constant, constant-random, and random-constant groups showed better performance in the adaptation phase than did the random group. In Experiment 2, the constant and constant-random groups performed better than did the others. And, in Experiment 3, the constant-random group demonstrated better performance than the others. Overall results indicated that, during the adaptive process of motor skill acquisition, constant and constant-random practice, were superior to random and random-constant practice.